Letter from Thomas Slater Price to Georg Bredig - Slater Price, Thomas, 1875–1949 (1900)
Letter from Thomas Slater Price (1875-1949) to Georg Bredig (1868-1944). Price, a British chemist, expresses his interest in returning to work with catalysts and asks Bredig for advice.
Keywords: Bredig, Georg, 1868-1944; Slater Price, Thomas, 1875–1949; Chemists; Catalysts